Unit of Measure in Tanjung Tanah Codes of Law - ZE, Deki Syaputra; Yarmayani, Ayu; Rahim, Arif; Afrila, Diliza; Pamungkas, Satriyo (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
As the oldest Malay manuscript in the world, Tanjung Tanah Codes of Law has many unique features not only from the physical form of the manuscript, but also related to the content of the manuscript. One of the many unique features of the contents of this manuscript is that it relates to units of measurement. In this article, the author identified these units of measurement, described and analysed them to obtain definitions of terms and equivalents of these units of measurement, either with the same units of measurement as in contemporary times or equivalents which correspond to today's units of measurement. Abstrak Sebagai naskah Melayu tertua di dunia, Kitab Undang-Undang Tanjung Tanah memiliki banyak keunikan. Tidak hanya dari bentuk fisik naskah, tetapi juga terkait dengan isi dari naskah tersebut. Salah satu dari banyaknya keunikan dari isi naskah tersebut diantaranya adalah berkitan dengan satuan ukuran. Dalam artikel ini, penulis akan mengidentifikasi satuan ukuran tersebut serta mendeskripsikan dan menganalisisnya. Sehingga memperoleh definisi dari istilah serta padanan dari satuan ukuran tersebut, baik dengan satuan ukuran yang sama dengan masa yang sezaman atau padananya yang sesuai dengan satuan hitungan hari ini.